Cinachyrella anatriaenilla sp. nov., a new tetillid sponge with microacanthoxeas from American Samoa in the South Pacific - Fernandez, Julio C.c.; Kelly, Michelle; Bell, Lori J. (Zootaxa, 2017)
Several sponges from American Samoa, collected by the Coral Reef Research Foundation, Republic of Palau, were tentatively identified by one of us as Acanthotetilla cf seychellensis (Thomas 1973), due to the possession of relatively small acanthose oxeas, compared to those of other species of the genus Acanthotetilla Burton 1959. These sponges were later compared to Cinachyrella australiensis (Carter 1886), taking into account the lack of conspicuous spination on the acanthose oxeas and general features of spiculation and skeletal organisation. The specimens were later considered to represent a new species of the genus Cinachyrella Wilson 1925, after a careful comparison was made between the American Samoan specimens and C. australiensis which also contains small acanthose oxeas. Several recent molecular phylogenetic studies have confirmed the generic assignment of one of the American Samoan specimens as belonging to Cinachyrella. Cinachyrella anatriaenilla sp. nov., described herein, is the fifth of 40 Cinachyrella spp. that contain lightly spined microacanthoxeas.